THE DISCRETE VORTEXES METHOD WITH THE IMPROVED QUADRATURE FORMULAE IN THE AEROELASTICITY PROBLEMS - V. V. Ovchinnicov; Y. V. Petrov; V. M. Popov (Научный вестник МГТУ ГА, 2016)
The possibility of the improved quadrature formulae of the discrete vortexes method used in the aeroelasticity problems is considered. Some of the calculation results confirm the efficiency of these formulae are carried out.